2021
DOI: 10.3390/geriatrics6030086
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status among Polymedicated Geriatric Inpatients at Discharge: A Population-Based Hospital Register Analysis

Abstract: This study explored and compared the functional status of polymedicated and non-polymedicated geriatric inpatients at hospital discharge. We used a cross-sectional registry of geriatric patients’ hospital records from a multi-site public hospital center in Switzerland. The analysis included all inpatients aged 65 years old or more admitted between 1 January 2015 and 31 December 2017 (n = 53,690), of whom 67.5% were polymedicated at hospital discharge, 52.1% were women (n = 18,909), and 42.7% were 75–84 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 62 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…However, little is known about the extent of older people's complex needs in the various domains relevant to health and care towards the end of life, that are, the physical, psychological, social, and spiritual domains. Previous research concerning older people upon hospital discharge mainly focused on their clinical characteristics and physical symptoms such as level of frailty [11], functional status [12,13], or on specific symptoms or concerns such as pain and anxiety [14]. But these data do not comprehensively cover the multidimensional needs and concerns relevant towards the end of life and their interrelationships.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the extent of older people's complex needs in the various domains relevant to health and care towards the end of life, that are, the physical, psychological, social, and spiritual domains. Previous research concerning older people upon hospital discharge mainly focused on their clinical characteristics and physical symptoms such as level of frailty [11], functional status [12,13], or on specific symptoms or concerns such as pain and anxiety [14]. But these data do not comprehensively cover the multidimensional needs and concerns relevant towards the end of life and their interrelationships.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed quantitative23 28 29 and qualitative43 44 findings have been published in previous papers. Therefore, this section connects and integrates both sets of findings (table 1) and draws conclusions on how the qualitative results help to explain and extend specific quantitative results.…”
Section: Resultsmentioning
confidence: 99%
“…After approval by the Human Research Ethics Committee of the Canton of Vaud and our partnering hospital, a database containing the latter’s electronic health records from 1 January 2015 to 31 December 2017 for all inpatients aged 18 years or more (n=1 05 243) was provided to the research team in early 2019. This database was used to explore the functional status of polymedicated older adult inpatients at discharge (n=53 690 hospitalisation records) 23. However, the hospital’s data warehouse required more time to extract the database containing inpatients’ medication lists, and an updated database was provided at the end of 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are also consistent with those of multiple studies that have identified polypharmacy as a risk factor for hospitalization, longer length of hospital stay, and mortality risk in older patients. [22][23][24] The lower readmission rate of 10.2% overall likely reflects the dramatic change in hospitalization and rehospitalization during the COVID-19 pandemic. The patterns of hospital readmission changed after COVID-19 became an important cause of hospitalization.…”
Section: Discussionmentioning
confidence: 99%